Position Determination for Dynamic Scenes With Unsynchronized Image Sequences - Kai Guo; Rui Cao; Chenyang Yue; Xin Zhou; Boyu Liu (IEEE Access)
Solving the stereo camera synchronization problem or estimating the temporal offset for dynamic scenes in triangulation is crucial in computer vision and photogrammetry. However, for cheap cameras like webcams, or cameras with long distance, synchronization is costly and complex. This paper proposed a novel method to determine 3D position for dynamic scenes with unsynchronized image sequences. For the proposed method, synchronized cameras are not essential, also, the temporal offset is not essential to be known. Additionally, it can be used for linear and curve motion, which provides a wider range of applications. In linear motion, the traditional triangulation is abandoned in this paper. Two planes can be determined with unsynchronized image sequences captured by two cameras and the intersection of the two planes is the motion trajectory. Also, one plane can be determined with unsynchronized image sequences captured by one camera, one ray can be determined with 2D projection captured by another camera, and the intersection of the plane and ray represents the current position. In curve motion, the correspondence points can be determined with epipolar line and 2D trajectory determined by unsynchronized image sequences, then the current 3D position is estimated by triangulation. This means using two completely independent cameras to capture dynamic scenes, our method can achieve determination under only ‘see’ and has nothing to do with other conditions (e.g., synchronization, frame rate). Compared to several SOTA (state-of-the-art) solvers, the experimental results show our proposed method performs robustly and high precisely.